2022
DOI: 10.3389/fonc.2022.908345
|View full text |Cite
|
Sign up to set email alerts
|

Functional lung imaging in thoracic tumor radiotherapy: Application and progress

Abstract: Radiotherapy plays an irreplaceable and unique role in treating thoracic tumors, but the occurrence of radiation-induced lung injury has limited the increase in tumor target doses and has influenced patients’ quality of life. However, the introduction of functional lung imaging has been incorporating functional lungs into radiotherapy planning. The design of the functional lung protection plan, while meeting the target dose requirements and dose limitations of the organs at risk (OARs), minimizes the radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…According to research results, there is heterogeneity in the distribution of lung function and inconsistent sensitivity to radiation. 61 A study by Vinogradskiy et al 62 showed that 4-dimensional computed tomography–based ventilation functional lung imaging-guided radiotherapy significantly reduced the incidence of grade 2 or higher RP. A study by Zhou et al 63 found that using functional lung protection in esophageal cancer radiotherapy planning was associated with decreasing functional lung mean dose by 1.5 Gy and volume of lung tissue receiving 20 Gy of more by 4.7%, without compromising planning quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to research results, there is heterogeneity in the distribution of lung function and inconsistent sensitivity to radiation. 61 A study by Vinogradskiy et al 62 showed that 4-dimensional computed tomography–based ventilation functional lung imaging-guided radiotherapy significantly reduced the incidence of grade 2 or higher RP. A study by Zhou et al 63 found that using functional lung protection in esophageal cancer radiotherapy planning was associated with decreasing functional lung mean dose by 1.5 Gy and volume of lung tissue receiving 20 Gy of more by 4.7%, without compromising planning quality.…”
Section: Discussionmentioning
confidence: 99%
“…RP is a common and severe toxic effect after radiotherapy in esophageal cancer. According to research results, there is heterogeneity in the distribution of lung function and inconsistent sensitivity to radiation 61. A study by Vinogradskiy et al62 showed that 4-dimensional computed tomography-based ventilation functional lung imaging-guided radiotherapy significantly reduced the incidence of grade 2 or higher RP.…”
mentioning
confidence: 99%
“…However, radiation-induced lung injury (RILI), such as radiation pneumonitis, is a common complication of lung RT and can affect the prognosis and life quality of patients (Hanania et al 2019). Functional lung avoidance radiotherapy (FLART) shows promise in reducing RILI by leveraging the heterogeneity of lung function distribution to selectively minimize dose to high functional lung (HFL) regions, thereby potentially enhancing lung function protection (Christian et al 2005, McGuire et al 2006, Ireland et al 2016, Faught et al 2017, Bucknell et al 2018, Vinogradskiy et al 2022, Zhou and Zhang 2022, Li et al 2023, Yamamoto et al 2023, in contrast to conventional anatomical image-guided RT which uniformly treats lung without function guidance.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant tumors remain one of the leading causes of death worldwide, and tumor prevention and treatment have increasingly become a major technological issue in the feld of life and health and the healthcare industry [1]. Radiation therapy is an efective tool used in the treatment of tumors, but it can cause normal tissue damage, especially lung injury after radiotherapy for breast cancer, lung cancer, or other malignant tumors of the chest [2]. In addition, many patients undergo synchronous chemotherapy to enhance the antitumor efcacy of radiation, which can lead to the exacerbation of lung injury, known as chemotherapy-induced lung injury (CILI) [3,4].…”
Section: Introductionmentioning
confidence: 99%